SIRT5 Promotes Cisplatin Resistance in Ovarian Cancer by Suppressing DNA Damage in a ROS-Dependent Manner via Regulation of the Nrf2/HO-1 Pathway - Sun, Xiaodan; Wang, Shouhan; Gai, Junda; Guan, Jingqian; Li, Ji; Li, Yizhuo; Zhao, Jinming; Zhao, Chen; Fu, Lin; Li, Qingchang (Frontiers in Oncology, 2019)
Sirtuin 5 (SIRT5), a mitochondrial class III NAD-dependent deacetylase, plays controversial roles in tumorigenesis and chemoresistance. Accordingly, its role in ovarian cancer development and drug resistance is not fully understood. Here, we demonstrate that SIRT5 is increased in ovarian cancer tissues compared to its expression in normal tissues and this predicts a poor response to chemotherapy. SIRT5 levels were also found to be higher in cisplatin-resistant SKOV-3 and CAOV-3 ovarian cancer cells than in cisplatin-sensitive A2780 cells. Furthermore, this protein was revealed to facilitate ovarian cancer cell growth and cisplatin-resistance in vitro. Mechanistically, we show that SIRT5 contributes to cisplatin resistance in ovarian cancer by suppressing cisplatin-induced DNA damage in a reactive oxygen species (ROS)-dependent manner via regulation of the nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase 1 (HO-1) pathway.